RESPON MAHASISWA PENDIDIKAN MATEMATIKA TERHADAP PENGGUNAAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN DARING[ - Vernita Sari (Tautologi: Journal of Mathematics Education, 2026)
YouTube, as a digital platform, has significant potential to support online learning because it provides engaging audio-visual content, is easily accessible, and allows students to review learning materials repeatedly. In addition, YouTube can increase students’ learning interest and create a more flexible learning experience. Therefore, lecturers are expected to be more creative in developing interesting, enjoyable, and interactive learning environments, and YouTube can serve as one of the effective media to achieve this goal. This study aimed to determine students’ responses toward the use of YouTube as an online learning medium. The findings are expected to serve as evaluation material for improving the learning process in the future. This research employed a descriptive quantitative design using a student response questionnaire to collect the required data. The results showed that the overall average percentage of all indicators reached 76.83% based on responses from 21 students of the Mathematics Education Study Program who completed the questionnaire. These findings indicate that Mathematics Education students had positive responses toward the use of YouTube as an online learning medium. Therefore, this positive response is expected to support students in carrying out the learning process more effectively and optimally. However, despite the positive responses, the use of YouTube as a learning medium still requires attention to several aspects, such as visual appearance, video quality, creativity in presentation, and the clarity of material delivery, in order to attract students and improve their understanding of the learning videos provided.